2023
DOI: 10.1021/acs.orglett.3c01217
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Diastereo- and Enantioselective [4 + 1] Cycloaddition of Hydroxyallyl Anilines with Sulfoxonium Ylides

Abstract: We present here an iridium-catalyzed diastereo-and enantioselective [4 + 1] cycloaddition reaction of hydroxyallyl anilines with sulfoxonium ylides under mild reaction conditions, leading to 3-vinyl indolines in moderate to good yields with excellent enantioselectivities. Control experiments disclosed a plausible reaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Other Lewis acids, i.e., Zn(OTf ) 2 , Yb(OTf ) 3 , ZnCl 2 , and FeCl 3 , were also tested, and they all successfully promoted reaction efficiency except ZnCl 2 , providing product 3a in 52-76% yields, respectively (Table 1, entries 9-12). Brønsted acids, such as TsOH, MsOH, and TFA, were further examined (Table 1, entries [13][14][15]. The results indicated that all the examined Brønsted acids showed significant promoting effect on the annulation and MsOH was proven to be the optimal acid, furnishing the desired product 3a in 89% isolated yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other Lewis acids, i.e., Zn(OTf ) 2 , Yb(OTf ) 3 , ZnCl 2 , and FeCl 3 , were also tested, and they all successfully promoted reaction efficiency except ZnCl 2 , providing product 3a in 52-76% yields, respectively (Table 1, entries 9-12). Brønsted acids, such as TsOH, MsOH, and TFA, were further examined (Table 1, entries [13][14][15]. The results indicated that all the examined Brønsted acids showed significant promoting effect on the annulation and MsOH was proven to be the optimal acid, furnishing the desired product 3a in 89% isolated yield.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, reductive elimination gives product 3a, with the regeneration of the palladium(0) species. According to previous literature, [11][12][13][14] the [4 + 1] annulation proceeds via the key zwitterionic intermediate C′ to form product 3a (Scheme 2, pathway b), which could not be ruled out, but pathway a is more convincing because it is difficult for the alkylamino group of 1a to form the corresponding amino anion under acidic conditions.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Sun et al reported the iridium-catalyzed diastereo- and enantioselective [4 + 1] cycloaddition reaction of a wide range of substituted hydroxyallyl anilines with aromatic and aliphatic sulfoxonium ylides 89 (Scheme ). The reaction is a straightforward way to synthesize highly substituted 3-vinyl indolines 91 containing two stereogenic centers in moderate to good yields with good diastereoselectivities (>19:1 dr in all cases) and excellent enantioselectivities. On the basis of experimental results, the reaction is believed to proceed via an AAA process that furnishes intermediate C from the π-allyliridium species B , followed by an intramolecular N -nucleophilic substitution that provides intermediate D and dimethyl sulfoxide.…”
Section: Ketones and Derivatives In The Catalytic Aaa Using Alcoholsmentioning
confidence: 99%